Successful treatment of IgA vasculitis with prolonged cutaneous manifestation with colchicine in a 10-year-old boy. Issue 1 (3rd November 2021) - Okura, Yuka; Hiramatsu, Yasuyoshi; Shimomura, Masaki; Taniguchi, Kota; Nawate, Mitsuru; Takahashi, Yutaka; Kobayashi, Ichiro
ABSTRACT: We report a 10-year-old boy with immunoglobulin (Ig)A vasculitis (IgAV) with prolonged cutaneous manifestations who was successfully treated with colchicine. At the age of 9 years, he was diagnosed as having IgAV by typical purpura, abdominal pain, and haematochezia. Initially, his severe gastrointestinal manifestation subsided by prednisolone 60 mg/day and intravenous methylprednisolone pulse therapy. However, his gastrointestinal manifestation was glucocorticoid-dependent and refractory to factor XIII concentrate, intravenous IgG, and mycophenolate mofetil. His abdominal pain and haematochezia responded to the combination therapy with dapsone and low dose of prednisolone 5 mg/day and did not relapse even after discontinuation of dapsone. On the other hand, the effect of dapsone on his cutaneous manifestation was dose-dependent as well as dapsone had no glucocorticoid-sparing effect. Approximately 12 months after onset, colchicine treatment was started, which resulted in remission of his chronic cutaneous manifestation. After prednisolone was tapered off, his cutaneous manifestation is currently well-controlled on colchicine 0.5 mg/day without adverse events. He had never complicated kidney involvements. In conclusion, it is observed that colchicine treatment exerts a beneficial effect in IgAV patients with prolonged cutaneous manifestation refractory to multiple drugs.